APLICAÇÃO DO CONCRETO DE ULTRA ALTO DESEMPENHO NA ARQUITETURA - Soriano, Amanda; Velasco, Reila (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
For many decades, the compressive strength of concrete remained in the range of 15 to 20 MPa, but the emergence of new materials and construction techniques, and the search for slimmer structural elements provided the development of more strength concrete. In this context, there is the ultra high performance concrete that allows a wide range of applications, both in engineering and architecture. This research therefore has to show the versatility of ultra high performance concrete in the field of architecture, through the production of a perforated panel, in order to simulate perforated façades. Sixteen traces of concrete were produced in order to obtain a concrete with strength and expected workability, according to the materials available in the laboratory. The concretes were characterized by compressive strength tests. The best performance concrete was used for the fabrication of the perforated panel prototype. All the constituents used for its production have led to a concrete with a capacity for density and compressive strength of more than 100 MPa. Such strength allowed the production of a panel with reduced sections, reinforcing one of the potentialities of ultra high performance concrete in architectural element.